Development of a polyallylamine hydrochloride hydrogel imprinted with xylose for the purification of xylose from sugar mixture. (23rd January 2023) - Liu, Jia; Song, Qianyi; Li, Youxin; Bao, James J.
Summary: A novel molecularly imprinted hydrogel (X‐MIP) was developed with poly (allylamine hydrochloride) as monomer and epichlorohydrin as crosslinker. After optimising preparation conditions including reaction temperature, the amount of NaOH and template xylose, the X‐MIP was characterised through Fourier transform infrared spectroscopy, scanning electron microscope and swelling ratio. Xylose and glucose were employed to evaluate the adsorption capacity and selectivity of the X‐MIP. Its adsorption to xylose followed pseudo‐second‐order rate kinetics and the adsorption process was multilayer adsorption based on the matched Freundlich isotherm model. Its adsorption capacity to xylose was up to 398.68 mg g −1 . The similar adsorption abilities in five successive runs and the good desorption rate (98.9%) verified its reusability. The selectivity for xylose and glucose could reach 4.70, and their separation factors in simulated xylitol production feedstocks were 591.05 (xylose:glucose, 99:1) and 15.42 (xylose:glucose, 3:1), respectively. Results indicated the prepared X‐MIP has good potential in industrial xylose purification. Abstract : A novel molecularly imprinted hydrogel (X‐MIP) with xylose was developed. It can distinguish xylose from sugar mixture and its adsorption capacity to xylose was high. It has good potential in industrial xylose purification.